Exemption From the Contractual Responsibility and The Extent of Its Legitimacy - Yas, Nadia; Alkuwaiti, Hareb Hamad Hareb (International Journal of Membrane Science and Technology, 2023)
Background and purpose – The purpose of this paper is to discuss the topic of exemption from contractual liability, with the examination of exemption and liability as the most important and dangerous conditions of a contract. Exemption from contract liability is to get out of the general rules requiring the debtor that has breached its contractual obligation to be liable as a result of such a breach. In the case of a contractual breach, the terms of exemption are exempted from the contractual liability or reduce the risks to the other contracting party. The researcher addressed the concept of contractual liability, its conditions and elements. Then, he clarified the legality of the exemption from the contractual liability through the conditions of exemption from liability and to indicate the position of the jurists on the extent to which the contract liability may be exempted and its effect on the contract. The importance of this study is reflected in the importance of determining contractual responsibility, as it is a fertile field for research in the field of the civil law and considered the backbone of the civil responsibility. Methodology - The researcher followed the analytical descriptive approach by talking about the ideas related to the topic. He used the comparative approach when comparing the position of the different legislations, examining and researching the meaning of the certain terms related to the study, and extrapolating them within the framework of laws and the opinion of the jurists therein. The researcher originally relied in his methodology on the previous studies, due to their importance in explaining the research and results that have been reached on the subject of the contractual responsibility. Accordingly, the research was divided into three sections, so that the first section dealt with the concept of contractual responsibility that divided into three requirements. While the second section touched on the legality of the exemption of the contractual liability, and there are three requirements. As for the third section, it was devoted to examining the effects of the condition from exemption of the contractual liability and the restrictions imposed on it, and it contains three requirements. Results and discussion - The subjects of utilization and work of common duty shift into numerous kinds, and this duty is separated into an authoritative obligation, and the standards and establishments of authoritative obligation are carried out in the event of an unlawful infringement in the details of the agreement. In the event that authoritative risks were not satisfied, it was feasible to carry out the guidelines of misdeed responsibility. The legally binding risk is discredited is conditions of the contract are not met. Conclusion - In this research, the researcher exposes certain concepts of contractual responsibilities, since it is a valid and legitimate way to relieve a party from certain obligations mentioned in a contract provided the actors have met certain legal requirements. The scientist clarified that the details of authoritative obligation are referenced in three conditions: the first being that there is a contractual bond between the responsible and the injured party, the second being that the contract is established validly and the third condition is that the responsible party breaches one of his contractual obligations, with damage occurring as a result of the breach.